2014
DOI: 10.1016/j.ydbio.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Unc45b is essential for early myofibrillogenesis and costamere formation in zebrafish

Abstract: Despite the prevalence of developmental myopathies resulting from muscle fiber defects, the earliest stages of myogenesis remain poorly understood. Unc45b is a molecular chaperone that mediates the folding of thick-filament myosin during sarcomere formation; however, Unc45b may also mediate specific functions of non-muscle myosins (NMMs). unc45b Mutants have specific defects in striated muscle development, which include myocyte detachment indicative of dysfunctional adhesion complex formation. Given the necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Thus, the response to unc45b deficiency may not entirely be mediated by Hsf1 and most likely includes a further amplification of the transcriptional response by these downstream TFs. Although the skeletal myosins are the most abundant myosins in the myofiber, we cannot exclude that misfolding of the non-muscle myosins, such as the myosins implicated in the formation of costameres mediating fibril attachment [ 21 , 23 ], co-determines the types of genes induced in the unc45b mutant. Interestingly, a significant number of genes involved in visual perception (such as Alpha crystallin A [ 67 ], CNGA3 [ 68 ], and RLBP1 [ 69 ]) are down-regulated in the unc45b mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the response to unc45b deficiency may not entirely be mediated by Hsf1 and most likely includes a further amplification of the transcriptional response by these downstream TFs. Although the skeletal myosins are the most abundant myosins in the myofiber, we cannot exclude that misfolding of the non-muscle myosins, such as the myosins implicated in the formation of costameres mediating fibril attachment [ 21 , 23 ], co-determines the types of genes induced in the unc45b mutant. Interestingly, a significant number of genes involved in visual perception (such as Alpha crystallin A [ 67 ], CNGA3 [ 68 ], and RLBP1 [ 69 ]) are down-regulated in the unc45b mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Unc45a has been shown to cooperate with Hsp90 in chaperoning mammalian progesterone receptor [ 18 ] and plays a role in pharyngeal and aortic development in zebrafish [ 19 ]. Unc45b was proposed to be required for the folding of myosins in general, including those myosins that are not part of the myofibril [ 20 , 21 ]. Missense mutations in unc45b have been associated with juvenile cataract in humans, a phenotype that is also evident in the unc45b zebrafish mutant [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to thick and thin filament defects, UNC-45b morphants displayed disrupted M-lines and Z-disks in sarcomeres of skeletal muscles, with a significant decrease in myosin protein levels (Bernick et al, 2010). Very recently, Myhre et al demonstrated that UNC-45b co-localizes with non-muscle myosins in zebrafish myogenic tissue prior to the expression of muscle myosin and that an unc-45b mutation disrupts costamere formation and attachment of muscle fibers to the tendon-like myosepta (Myhre et al, 2014). Thus UNC-45b may be important for non-muscle myosin folding at very early stages of muscle development (Myhre et al, 2014), a role that might have been attributed to UNC-45a due its widespread expression and its necessity for myoblast proliferation (Price et al, 2002).…”
Section: Model Organism-based Studies Of Unc-45 Functionmentioning
confidence: 99%
“…Knockdown of either form of Apobec2 results in reduced motility, impaired cardiac function, skeletal myofibril disorganization and disrupted muscle fibers and myosepta (tendon equivalents). Apobec2 was shown to co-localize with UNC-45b to the myoseptal boundary and the Z-disks (Etard et al, 2010; Myhre et al, 2014). Although the localization of UNC-45b was not dependent upon the presence of Apobec2, the localization of Apobec2 does depend upon UNC-45b, implicating UNC-45b in muscle fiber attachment to the myoseptum (Etard et al, 2010).…”
Section: Model Organism-based Studies Of Unc-45 Functionmentioning
confidence: 99%
See 1 more Smart Citation